An update on the ant-mimicking genus Corinnomma Karsch, 1880 (Araneae, Corinnidae, Castianeirinae) - Sankaran, Pradeep M. (Zootaxa, 2023)
The castianeirine species Corinnomma moerens Thorell, 1890, and C. plumosum (Thorell, 1881), both known only from textual descriptions, are redescribed and illustrated based on the type material. Type images for Corinnomma javanum Simon, 1905, C. severum (Thorell, 1887), and C. thorelli Simon, 1905 are presented to facilitate identification along with supplementary descriptions of the types, and the distribution of the species C. simplex Zhang, Jin & Zhang, 2022 is updated.